2011
DOI: 10.3382/ps.2009-00616
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in the liver tissue of geese after overfeeding

Abstract: Geese form a fatty liver after feeding on a carbohydrate-rich diet, possibly as an evolutionary adaptation to accumulate reserves for migration. To gain insight into the gene-regulation processes of hepatic steatosis in geese, we examined the profile of transcriptional expression in goose fatty liver and control liver by suppression subtractive hybridization and measured the levels of serum biochemical variables. We found 107 genes whose expression was different between the treatment and control groups. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 43 publications
3
46
1
Order By: Relevance
“…We and others previously demonstrated overfeeding could induce dramatic upregulation of genes for de novo lipogenesis in goose liver [17,18], which is consistent with the notion that the liver is the major site of de novo lipogenesis in avian species. Insulin induces strong effects on lipid accumulation, expression of genes for lipogenesis, fatty acid oxidation, and very low density lipoprotein (VLDL)-triacylglycerol (TG) assembly and secretion in primary goose hepatocytes [19,20], and hyperinsulinemia is closely linked to insulin resistance.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…We and others previously demonstrated overfeeding could induce dramatic upregulation of genes for de novo lipogenesis in goose liver [17,18], which is consistent with the notion that the liver is the major site of de novo lipogenesis in avian species. Insulin induces strong effects on lipid accumulation, expression of genes for lipogenesis, fatty acid oxidation, and very low density lipoprotein (VLDL)-triacylglycerol (TG) assembly and secretion in primary goose hepatocytes [19,20], and hyperinsulinemia is closely linked to insulin resistance.…”
Section: Introductionsupporting
confidence: 84%
“…The data suggested overfeeding did not induce ERS in the occurrence of goose fatty liver. As our previous studies demonstrate goose fatty liver is dominated by unsaturated fat rather than saturated fat [18] and unsaturated fat suppresses ERS [22], we speculated that the lack of ERS induction in goose fatty liver was due to the upregulation of enzymes involved in fatty acid desaturation. Indeed, we demonstrated the expression of fatty acid desaturases (Fads 1,2 and 6) were increased in the livers of overfed geese vs. normally-fed geese (Fig.…”
Section: Overfeeding Induced Systematic Glucose Intolerance and Fattymentioning
confidence: 97%
“…To better understand the adaptive mechanisms developed by hepatocytes in response to large carbohydrate intake, Bax et al [35] investigated proteome modifications during steatosis development in duck. At the end of the overfeeding period, the genes involved in the synthesis of triglycerides and fatty acids are over expressed, and those involved in the β-oxidation are under expressed in goose [32] and duck [31]. The results on the genes involved in glycolysis are contradictory between the Table 1 -Comparison of the differentially expressed proteins [27,28] or transcripts [27] two studies.…”
Section: Liver Proteome Of Waterfowlmentioning
confidence: 85%
“…The expression levels of genes involved in lipid and carbohydrate metabolisms, and their regulations, were compared between Muscovy and Pekin ducks [31]. Gene expression profiles were also examined in Landes geese before and after overfeeding [32]. Despite the fact that proteins represent only 5 to 7% of the fresh matter in fatty liver [33,34], they play a key role in the metabolism of the liver and particularly during the adaptation phase when the liver faces an increase in glucose uptake because of the very large quantities of corn ingested.…”
Section: Liver Proteome Of Waterfowlmentioning
confidence: 99%
“…Yu et al (2011) used genome microarray analysis and found that the differentially expressed genes between fetal ventricular septal defects in the myocardium and normal myocardium were related to signaling pathways in heart development. In recent years, the application of microarray technology has also extended to agriculture, such as for studying rice, flax, poplar, chickens, cattle, and geese (Cogburn et al, 2003;Arora et al, 2007;Zhao., 2010;Long et al, 2011;Zhu et al, 2011;Guifen et al, 2012). Real-time fluorescent quantitative PCR is necessary to ensure the reliability of the chip (Canales et al, 2006), and was used in the current study to test and verify some of the differences in gene expression.…”
Section: Discussionmentioning
confidence: 99%